The Correlation Between Pregnant Women Knowledge About Covid-19 and Its Transmission Prevention Behavior During Pregnancy - Hanum, Rezma Latifah; Fitriana, Farida (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2022)
Background: Coronavirus Disease (COVID-19) is an infectious disease that can be transmitted from human to human through coughing/sneezing droplets (droplets). Pregnant women are a group that is vulnerable to the risk of being infected with COVID-19, furthermore it is necessary to take some preventive actions toward COVID-19. According to the literature review and previous research, knowledge is one of the factors that influence health behavior.Objective: This study aims to determine the correlation between knowledge of pregnant women about COVID-19 and the behavior to prevent transmission.Methods: The type of research method is cross-sectional. The samples in this study were all populations that met the inclusion and exclusion criteria with consecutive sampling techniques. The independent variable of this study is the knowledge of pregnant women about COVID-19 and the dependent variable is prevention behaviorResults: Based on the results of this study, showed that the majority of respondents have good knowledge, 33 people (73.3%) and have good behavior in preventing COVID-19, 34 people (74.6%). The results of the bivariate analysis showed that there was a correlation between the knowledge of pregnant women about COVID-19 and its prevention behavior during pregnancy.Conclusion: The majority of respondents have good knowledge and have the behavior of preventing the transmission of COVID 19 in the good category. Besides, there is a significant correlation between the knowledge and behavior to prevent transmission of COVID 19 with p value of 0.001 (p value <0.05).